Navigating new normals: the influence of COVID-19 policies on community access and well-being of people with mobility disabilities in everyday life - Wendel, Carrie L.; Gray, Randi Christine; Goddard, Kelsey; Hall, Jean P. (Frontiers in Public Health, 2024)
Context This study explores the influence of COVID-19 public health mandates on people with mobility disabilities in the United States in their everyday lives. It highlights the intersection of disability with social determinants of health, emphasizing the need for a comprehensive policy response. Methods Qualitative data were collected through 76 semi-structured interviews with people with mobility disabilities. Interviews focused on experiences with COVID-19 mandates and community access, analyzed using thematic analysis and coded for emergent subthemes. Results The relationship between community participation and COVID-19 compliance was complex for people with disabilities. Inaccessible environments and inflexible policies made it difficult for people with disabilities to practice good safety measures, while widespread noncompliance by community members limited their community participation. The findings revealed additional mixed lived experiences of COVID-19 policies on community participation, accessibility, and access to resources and support. While technology facilitated some aspects of community participation, issues with accessibility, public transportation, and personal assistance services were exacerbated. Conclusion COVID-19 policies have complex implications for people with mobility disabilities. Findings suggest a need for inclusive policymaking, improved disability awareness, and continued support for accessible technology and services. Future research should further explore these dynamics to inform policy and practice.